Search for meteoritic GEMS I: Comparison of amorphous silicates in Paris and Acfer 094 chondrite matrices and in anhydrous chondritic interplanetary dust particles. (1st October 2021) - Ohtaki, Kenta K.; Ishii, Hope A.; Bradley, John P.; Villalon, Krysten L.; Davis, Andrew M.; Stephan, Thomas; Bustillo, Karen C.; Ciston, Jim
Abstract: Amorphous silicates in meteoritic samples are significant as potential surviving interstellar dust from the formation of the Solar System. Amorphous silicate-rich grains called GEMS, glass with embedded metal and sulfides, are abundant in anhydrous interplanetary dust particles and some ultracarbonaceous Antarctic micrometeorites that have high presolar grain abundances. Some GEMS within these objects have been confirmed to be presolar. GEMS-like material, consisting of amorphous silicate with opaque inclusions, has been identified in the matrices of some primitive meteorites. We use specialized thin specimen preparation and transmission electron microscopy methods to compare the GEMS-like material in Paris (CM) and Acfer 094 (ungrouped) chondrites with GEMS in anhydrous, chondritic interplanetary dust particles. Specifically, we compared the amorphous silicate morphology, degree of partial ordering, elemental composition and dominant iron oxidation state. We find that the amorphous silicates in the GEMS-like materials in Paris and Acfer 094 show incipient ordering and are Fe-rich and highly oxidized, while those in GEMS are fully amorphous, Fe-poor, and anhydrous. From examination of various formation routes for the amorphous silicates, we conclude that the GEMS-like material in Paris and Acfer 094 is not GEMS and that it is unlikely that GEMS-like material accreted as primary amorphous material that retained its original amorphous structure since accretion. We also conclude that the presence of GEMS-like amorphous silicates in chondrite matrix is not a reliable indicator for high degrees of primitivity or pristinity since even mild, complex alteration processes may significantly alter silicate structure. Finally, we propose searches for presolar amorphous silicates in chondrite matrix samples that have been precharacterized by transmission electron microscopy methods to enable direct comparisons of presolar amorphous silicate abundances.